Pengujian Bakteri Potensial Pendegradasi Dibenzothiophene (DBT) yang diisolasi dari Tanah yang Terkontaminasi Minyak Bumi di Samboja - Issassam, Bimby; Wayan Gunam, Ida Bagus; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 3 (2016): September, 2016)
This study aims  to determine the  dibenzothiophene (DBT)  degradation  level  of  four potential sulfur aromatic degrading bacteria. Biodesulfurization activity test was done by using twophase system. First was water phase  which used mineral salt sulfur free (MSSF) medium and the second phase was oil phase which use 200 ppm DBT in n-tetradecane. Isolates were incubated for 96 hours at 37 o C  and the DBT residu oil phase was analyzed using  Gas Chromatography. The experiment was repeated twice. This isolate wa able to degrade DBT in level of 80,82% after 96 hours incubation. The growth of the bacteria in water phase reached OD 660 1,169. Keywords: Dibenzothipohene, Biodesulfurization, Bacteria Potential, SBJ 8
Keywords: 103